Participación de niñas, niños y adolescentes como sujetos activos del delito, generando un factor delictivo criminológico alarmante para la sociedad actual - Aranda Torres, Viviana Ivette (2017)
The causes of crime have changed over the years and the development of societies; hence, criminologists have been echoed by various currents to give explanation to this phenomenon, sometimes contradictory. Ecuadorian society is currently facing a problem of social and juridical character, which has to do with participation, increasingly frequent in children and adolescents, as perpetrators of the crime, constituting this a serious criminological phenomenon that must be studied and analyzed in order to raise a legal proposal in this regard. Currently the participation of children and adolescents as perpetrators of the crime, is a constant in major cities across the country, so it would be suggestive to be revised the existing legal constitutional regime and, as one of the root causes for this is criminological phenomenon is the criminal responsibility of minors in force in Ecuador, which makes many children as teenagers, are recruited into organized criminal organizations, so that they are responsible for committing crimes. Considering the condition of group focus that characterizes children and adolescents of Ecuador, can be socially justify the development of the study I propose, as the participation of children and adolescents as active subjects of offenses criminal, is a problem that causes alarm and insecurity in Ecuadorian society. The National University of Loja in different areas of study, is implementing an academic system through the development of the Research of Social Problems, Legal and Cultural surrounding our reality, and based on this research to present alternative solutions to live in an environment of peace, security and tranquility that is what is enshrined in our Constitution, through proper and flexible application of legal rules that are stipulated in the laws of the Republic. This project is feasible from every point of view, as it has the necessary resources such as documents, guides, library materials, library service, collaboration of legal professionals, the orientation of Tutor Teaching, especially the dedication and the will to meet goals. This research is governed by the precepts of the School of Law, for identifying this problem the respective steps and the academic requirements of the National University of Loja was followed.